DIAGNOSIS AND TREATMENT OF ACUTE ACHILLES TENDON RUPTURE: A COMPREHENSIVE SYSTEMATIC REVIEW - Rapmartua Ompusunggu, Indra Hadi; Yulanda Putra, Yosie; Auliya, Ahsan (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Achilles tendon rupture is a common orthopaedic injury that results in substantial functional limitations throughout a lengthy recovery time. The increasing incidence of Achilles tendon ruptures has been well documented in population-based studies. The delayed treatment of AT ruptures is usually attributable to either poor diagnosis upon injury or patients disregarding their injuries and not presenting to healthcare facilities. The aim: The aim of this study to show about diagnosis and treatment of acute achilles tendon rupture. Methods: By the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. This search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed, SagePub, and Google Scholar were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search get 17 articles, whereas the results of our search on SagePub get 299 articles, on Google Scholar 6990 articles. Records remove before screening are 5317, so we get 1989 articles fos screening. After we screened based on record exclude, we compiled a total of 12 papers. We included five research that met the criteria. Conclusion: Multiple evaluative techniques including the addition of diagnostic ultrasound imaging and continuous shear wave elastography (cSWE) to standard clinical tests and measures were used to assess patient-reported symptoms, tendon structure, and tendon functional performance. As treatment recommendations and strategies evolve, decisional conflict may arise when patients with Achilles tendon ruptures are faced with the need to choose a management option. There have been several reviews of management strategies, primarily focused on pairwise comparisons between individual operative and non-operative strategies.